2007
DOI: 10.1111/j.1469-8137.2007.02027.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 concentration and diurnal cycle induce changes in lipid composition in Arabidopsis thaliana

Abstract: Summary• Few studies regarding the effects of elevated atmospheric CO 2 concentrations on plant lipid metabolism have been carried out. Here, the effects of elevated CO 2 concentration on lipid composition in mature seeds and in leaves during the diurnal cycle of Arabidopsis thaliana were investigated.• Plants were grown in controlled climate chambers at elevated (800 ppm) and ambient CO 2 concentrations. Lipids were extracted and characterized using thin layer chromatography (TLC) and gas liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 54 publications
6
27
0
Order By: Relevance
“…The relative composition of microalgal lipids depends greatly on the species used and the nutrient, environmental, and developmental conditions in which the cells are cultured and harvested. It has been reported that the composition of microalgal lipids varies considerably with the growth cycle, under nutrient limitation and during a diurnal light dark cycle (Sukenik and Carmeli 1990;Ekman et al 2007). For example, Nannochloropsis sp.…”
Section: Biodieselmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative composition of microalgal lipids depends greatly on the species used and the nutrient, environmental, and developmental conditions in which the cells are cultured and harvested. It has been reported that the composition of microalgal lipids varies considerably with the growth cycle, under nutrient limitation and during a diurnal light dark cycle (Sukenik and Carmeli 1990;Ekman et al 2007). For example, Nannochloropsis sp.…”
Section: Biodieselmentioning
confidence: 99%
“…The traditional wastewater treatment ponds can be modified by creating a controlled anaerobic environment such as a covered pond or tank which allows the methane to be captured and combusted for energy production. In the biochemical process of anaerobic digestion, the waste goes through three steps namely hydrolysis, fermentation and methanogenesis as it is converted to methane (Metcalf and Eddy 2003). Anaerobic digestion is a very effective process for biological oxygen demand removal but it is not an effective way to remove nutrients.…”
Section: Biomethanementioning
confidence: 99%
“…The relative composition of algal lipids depends greatly on the species used and the nutrient, environmental and developmental conditions in which the cells are cultured and harvested. For example, it has been shown that the composition of algal lipids varies considerably with the growth cycle, under nutrient limitation and during a diurnal light dark cycle (Shifrin & Chisholm 1981;Cho & Thompson 1986;Sukenik & Carmeli 1990;Ekman et al 2007). It remains to be seen how the composition of the lipids affects the efficiency of biofuel conversion.…”
Section: Types and Function Of Lipids In Microalgaementioning
confidence: 99%
“…Biomass productivity in outdoor ponds is presented in Table 2 and has been adapted from a review by Griffiths and Harrison (2009 Lipids are abundant in many algae. Lipids and fatty acids serve as key components for cell membranes in plants and algae as well as being important for chemical signaling and energy storage (Ekman et al 2007). Environmental factors such as temperature, light cycles, and nutrient deprivation can influence the capacity for lipid synthesis (Roessler 1988;Shirffrin and Chisholm 1981;Sukenik et al 1989).…”
Section: Composition and Oil Contentmentioning
confidence: 99%